АLЕGISLАTIVЕ NАTURЕ АND DIRЕCTIОN ОF MОDЕRNIZАTIОN ОF АGRОINDUSTRIАL CОMРLЕX (Journal of actual problems of jurisprudence, 2019)
In this article theoretical and practical aspects of legal status of agro-industrial complex (АPK) in Kazakhstan are considered. The agro-industrial complex unites all industries which are taking part in production of agricultural products, its processing and bringing to the consumer. Kazakhstan, owing to natural, climatic and geographical features and also specific conditions and traditional labor skills of indigenous people inherent in it, long since is considered one of the largest livestock countries. In Kazakhstan nearly a half of the population lives in the village, but agriculture became the weakest industry which demands correctly picked up consecutive approach to reforming. Now sustainable development of agro-industrial complex is considered as the complex generalizing criterion of successful activity as in general national economies, and the separate industries, and effective activity of APK most fully is equitable to the interests of producers, consumers and potential investors. Authors focus attention to relevance of the studied problem, define the place and a role of agroindustrial complex in economy of Kazakhstan and also author’s definition by comparison of various points of view of scientists is given and offers ways of improvement of the current legislation in the field. In article the difficult and many-sided questions of productive and economic, organizational, social and legal character requiring the comprehensive solution and making problems of development of agroindustrial complex of the Republic of Kazakhstan are considered. As the most significant are allocated problems of creation of new more perfect production facilities, high-quality change of the relations of productive and economic character between subjects of economy. The increasing nonequivalence of barter of the branches of agriculture with other industries is noted. It is revealed that one of the reasons of low labor efficiency level in agriculture is the high moral and physical wear of the equipment and fixed assets. Besides, problems of providing the favorable environment with the state for the purpose of effective functioning of agrarian production which has to be implemented through certain functions are analyzed. Formation and reproduction of effective subjects of the market relations has to become the most important function of the state. At the same time the role of the state has to come down to that by means of scientifically based forms, methods, levers, preparation and retraining of personnel to create a favorable environment for steady reproduction of effective subjects of the market relations in APK of the Republic of Kazakhstan, its regions, enterprise structures. Key words: agro-industrial complex, agrarian legislation, agriculture, agricultural cooperative, food security of the country, production efficiency, agrarian legal relationship, land law, ecological right, state mechanism.